Chronic Rhinosinusitis Disease Disparity in the South Florida Hispanic Population. (13th July 2021) - Levine, Corinna G.; Casiano, Roy R.; Lee, David J.; Mantero, Alejandro; Liu, Xue Zhong; Palacio, Ana M.
Abstract : Objectives/Hypothesis: The role of social determinants of health in chronic rhinosinusitis (CRS) is poorly characterized. Limited research examining CRS health disparities indicates that minority status is associated with worse CRS. However, many of these studies are retrospective or performed in populations without substantial ethnic minorities. Rhinologists need to characterize existing CRS disease disparities to develop targeted strategies for improving care in these populations. This prospective study assesses preoperative CRS disease burden in South Florida (SFL) Hispanic and non‐Hispanic patients and examines potential factors contributing CRS disease disparities. Study Design: Prospective cohort study. Methods: The prospective cohort study included consecutive patients having primary endoscopic sinus surgery (ESS) for CRS between September 2019 and February 2020 with complete preoperative data. Data were collected in clinic and surgery. Descriptive statistics compare Hispanic and non‐Hispanic cohorts. Linear regression adjusts for confounders. Relative risk (RR) compared CRS severity markers. Results: Thirty‐eight Hispanic and 56 non‐Hispanic patients met inclusion criteria. Age, sex, CT scores, insurance payer, and comorbidities were similar between cohorts. Hispanics presented with worse 22‐item Sinonasal Outcome Test (SNOT‐22) (55; SD = 18) compared to non‐Hispanics (37; SD = 22) ( P < .001). Hispanics tended to have a higher risk of severe CRS markers, including nasal polyps RR = 2.5 (95% CI: 1.0–5.9), neo‐osteogenesis RR = 1.6 (95% CI: 0.5–4.7), extended procedures (i.e., draft III) RR = 2.97 (95% CI: 1.0–9.1), and tissue eosinophilia RR = 1.46 (95% CI: 0.6–3.5). Hispanics reported longer sinonasal symptom duration. Conclusions: SFL hispanic patients presenting for primary ESS have worse sinonasal disease burden. SFL Hispanics have markers of greater CRS severity and report longer delays before receiving CRS care. These factors may contribute to increased sinonasal disease burden in Hispanic patients. Level of Evidence: 3 Laryngoscope, 131:2659–2665, 2021